Growing Customer Loyalty Through Excellent Service And Business Ethics - Siti Fatimah (BJRM (Bongaya Journal of Research in Management), 2021)
The studyy aims to test: Thee influencee of leadership and task demands oon organizational commitment. This research approach is quantitative. The populasi in the study were all employees who were at PT. MAKASSAR TIMUR. The sample of this study were 44 employees in the PT. MAKASSAR TIMUR,using multiple linear regression analysis. From the analysis model, the value of the dependent variable was obtained from the results of the questionnaire and used a Likert scale. The results of this study indicate that: The results of hypothesis testing using multiple linear regression analysis indicate that the model under study has met the model's feasibility test. Where the variable (X1) good leadership shows positive and significant results on Organizational Commitment, then the variable (X2) Task Demands shows negative and insignificant results on Organizational Commitment. Then, based on partial testing, it shows that the two independent variables, namely leadership and task demands, have an effect on organizational commitment.”